2010
DOI: 10.1111/j.1365-2656.2010.01765.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermally contingent plasticity: temperature alters expression of predator-induced colour and morphology in a Neotropical treefrog tadpole

Abstract: Summary1. Behavioural, morphological and coloration plasticity are common responses of prey to predation risk. Theory predicts that prey should respond to the relative magnitude of risk, rather than a single level of response to any risk level. In addition to conspecific and predator densities, prey growth and differentiation rates affect the duration of vulnerability to size-and stage-limited predators and therefore the relative value of defences. 2. We reared tadpoles of the Neotropical treefrog Dendropsophu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 82 publications
(166 reference statements)
2
27
0
Order By: Relevance
“…Our result that warming facilitated growth more than development in the presence of predators is partly consistent with Touchon and Warkentin (2011), who show that warming facilitated tadpole development (but not growth) in the presence of predators, but seems contrary to established metamorphosis theories. For example, the Wilbur and Collins (1973) model predicts that increased growth rate is associated with slower development.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Our result that warming facilitated growth more than development in the presence of predators is partly consistent with Touchon and Warkentin (2011), who show that warming facilitated tadpole development (but not growth) in the presence of predators, but seems contrary to established metamorphosis theories. For example, the Wilbur and Collins (1973) model predicts that increased growth rate is associated with slower development.…”
Section: Discussionsupporting
confidence: 71%
“…Moreover, our study lasted for 13 weeks, and it is one of the few experimental studies reporting warming effects on timing and size at metamorphosis of tail resorption. The two studies that explicitly addressed the interaction between predators and warming (Laurila et al 2008;Touchon and Warkentin 2011, as noted in Introduction) were accomplished within a short time (\30 days).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, our study is not the only case violating this dogma. Touchon and Warkentin [22] also found that the single warming effect on tadpole growth was not significant in Neotropical treefrog Dendropsophus ebraccatus over a three-week long experiment. Moreover, Alvarez and Nicieza [21] reported that tadpole body mass of the Iberian Painted Frogs ( Discoglossus galganoi ) varied inversely with temperature under non-limiting food availability.…”
Section: Discussionmentioning
confidence: 95%
“…For example, long-term field monitoring programs [16], [17] have revealed that tadpoles grow faster in warm years than in cold years; large spatial-scale investigations have shown that the growth rate of tadpoles progressively increases across the gradients from high to low latitudes or altitudes [18][20]; laboratory studies have also indicated that amphibian tadpoles grow faster at high temperatures [5], [21], [22]. Another issue is that many predator species preying on tadpoles are gape-limited killers such as diving beetles (e.g.…”
Section: Introductionmentioning
confidence: 99%